Food, Land and Water Policies database, Lao PDR - Phongoudome, Chansamone; Sonethavixay, Sengpachanh (Lao National Database on Food Land and Water Policies, 2022)
Report No. 2: Collection of policies and database on food, land and water systems in Lao PDR (as 20 December 2022).